Analysis of the Utilization of Mangrove Species Diversity in Jerowaru District, East Lombok - Aminuddin, Muhammad (Lembaga Riset Mutiara Akbar, 2025)
Indonesia has the largest mangrove ecosystem in the world, but it experiences significant degradation of up to 52,000 hectares per year due to anthropogenic pressures and weak local governance. This condition demands a sustainable utilization strategy. This study examines the utilization of mangrove diversity by coastal communities in Jerowaru District, East Lombok, as a locally based conservation effort. A qualitative approach was used through participant observation, in-depth interviews, and field documentation, with thematic analysis to uncover adaptation patterns and perceptions of sustainability. The results indicate five dominant species—Rhizophora apiculata, Rhizophora mucronata, Avicennia marina, Bruguiera gymnorhiza, and Sonneratia alba—that are distributed across various ecological zones. Utilization includes construction materials, local food, herbal medicine, tourist attractions, and ritual activities, carried out collectively with traditional knowledge. Ecologically, mangroves function as abrasion barriers, waste filters, and habitats for coastal biota; socio-culturally, they serve as symbols of community identity and a space for intergenerational reflection. This study emphasizes the importance of integrating scientific and local knowledge as key to sustainable mangrove management. The utilization model in Jerowaru offers an integrated conservation approach that supports the Sustainable Development Goals (SDGs) while strengthening the foundations of a community-based green economy.